Pelatihan Mp-Asi Pangan Berbasis Lokal Dalam Peningkatan Pengetahuan Ibu Dan Status Gizi Pada Anak Dibawah Dua Tahun Di Wilayah Puskesmas Kabupaten Minahasa Tenggara - Nita R. Momongan; Olfie Sahelangi (POLTEKKES KEMENKES MANADO, 2018)
Appropriate supplementary food breast milk should start at 6 months of age, but the reality in many infants under 6 months has been given food. According to data Riskesdas 2013, North Sulawesi Province of malnourished status of 3.7% (National 5.7%) and nutritional status less 12.8% (National 13.9%). Results of Nutrition Status Monitoring (2015) North Sulawesi Province, nutrition sufferer less 10.6%, for stunting case with very short category North Sulawesi Province 6.3%, and short category 15.%. The purpose of this research is to know mother knowledge and nutritional status of children under two yearsbefore and after getting training of local food-based supplementary food breast milk in South Minahasa Regency.The research type is quasi experiment with pre and post design control group design. This study was conducted in the area of ​​Puskesmas district South Minahasa in June to September 2017. The population in this study were all mothers with children aged 12 to 24 months. Total sample amounted to 70 samples consisted of treatment group 35 samples and control group 35 samples and how to determine the sample size by Simple random sampling. Bivariate analysis used different test of two groups in pairs and inter-group different test. Result of research and conclusion: There is significant difference of knowledge of Baduta mother before and after training of local food-based supplementary food breast milk. There was no significant difference in nutritional status of Baduta children before and after local food-based supplementary food breast milk.